[Cu(HF2)(pyz)2]BF4 (pyz = pyrazine): long-range magnetic ordering in a pseudo-cubic coordination polymer comprised of bridging HF2- and pyrazine ligands. - Manson, J; Conner, M; Schlueter, J; Lancaster, T; Blundell, S; Brooks, M; Pratt, F; Papageorgiou, T; Bianchi, A; Wosnitza, J; Whangbo, M (2006)
[Cu(HF2)(pyz)2]BF4 consists of rare mu(1,3) bridging HF2- anions and micro-pyrazine ligands leading to a 3D pseudo-cubic framework that antiferromagnetically orders below 1.54(1) K.